O direito inquisitorial no regimento português de 1640: a formalização da intolerância religiosa (1640-1774) - Jácome, Afrânio Carneiro (2014)
Within the perspective of Cultural History this research proposes an analysis of a very important document for the History of the Inquisition in Portugal: the inquisitorial Regiment of 1640.This inquisitorial code lasted for 134 years of the 285 years of the Inquisition in Portugal, was compiled during the troubled process of restoration of the portuguese throne and replaced at the end of the controversial Pombal s period. For more than a century the Regiment dictated procedural rules and practices of the Holy Office lusitanian, their rites and labels, your public and private ceremonies; regulated on the application of punishments and served as a moral and religious teaching in the parameter control of the Inquisition under the lusitanian society and its colonies. We have described the Regiment of 1640 as the result of a long historical process. We discuss the idea of Law and Intolerance that have been shaping up in accordance with the economic, social and political factors that are constantly reconfigured through Europe during the scenarios of Middle and Modern Ages and, from these historical changes, walked the long hike until the Modern Inquisition in Portugal; their influences, struggles, conflicts, power relations and socio-cultural impacts. We trace a brief history of the Inquisition s codes, through a comparative analysis in order to better situate in relation to legal changes that converged in the Regiment of 1640. We contextualize the time of writing of 1640 regimental code. We analyzed the obstacles and the contexts of Iberian Peninsula and the inquisitorial real agents who moved in the intricate diplomatic game to redraw the boundaries after the independence of Portugal from Spain. We explore the importance of the central figures of the Inquisition in Portugal during the Portuguese Restoration s strife. We detail each of the three books that make up the regimental code: the book of ministers and officials, the book of procedural practices and the book of feathers. The analysis of the books was made with the intention of presenting the regimental details, the rich detailing of Inquisitorial Law and its justifications for its practical and specific penalties applications. When we historicizing the Inquisitorial Law, we verified its proximity to the Canon Law and its influence on the future development of a secular, scholar and written Law. In Portugal, the limits of Inquisitorial Justice and Secular Justice during the sixteenth, seventeenth and eighteenth centuries were not clear, observant of the of the monarchy s servants and agents of faith, on many occasions, their eyes walked together on their inspections in Portuguese territory and its colonies. The Roman Curia and the Portuguese Crown divided their influences under inquisitorial features, the real power applied its political and economic power within a regionalized perspective and the papacy outlined the legal and administrative functions of the Holy Office using its supranational power.